2018
DOI: 10.1039/c8fo00297e
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantiaextracts protect against inhibition of endothelial angiogenesis by advanced glycation endproductsin vitro

Abstract: Momordica charantia extracts protect against advanced glycation endproduct-induced anti-angiogenisis in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…The high systemic blood glucose concentrations resulting from diabetes lead to non-enzymatic glycation of proteins and the formation of AGEs [ 3 , 33 ]. AGEs enhance macrophage polarization to the M1 phenotype and inhibit the proliferation of fibroblasts, resulting in the formation of a pro-inflammatory environment that hampers angiogenesis and re-epithelialization, leading to a non-healing wound [ 4 , 34 , 35 ]. Moreover, diabetic non-healing wounds are easily infected by bacteria, which accelerate and aggravate the pathology of the diabetic wound [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high systemic blood glucose concentrations resulting from diabetes lead to non-enzymatic glycation of proteins and the formation of AGEs [ 3 , 33 ]. AGEs enhance macrophage polarization to the M1 phenotype and inhibit the proliferation of fibroblasts, resulting in the formation of a pro-inflammatory environment that hampers angiogenesis and re-epithelialization, leading to a non-healing wound [ 4 , 34 , 35 ]. Moreover, diabetic non-healing wounds are easily infected by bacteria, which accelerate and aggravate the pathology of the diabetic wound [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the hypoxic environment under moist wound dressings increased capillary proliferation; angiogenesis is faster in moist conditions (Boateng and Catanzano, 2015). In an in vitro study conducted by Aljohi et al (2018), it was reported that the methanolic extract of bitter melon had angiogenic effects. Singh et al (2017) reported that extracts of bitter melon topically can increase angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists claimed that it stimulated tube formation from bovine aortic endothelial cells (BAEC) to promote angiogenesis. 110 As one step further, injectable platelet‐rich fibrin (PRF) with a co‐culture of OECs (sprouting endothelial cells) and primary osteoblasts (pOBs) was found to represent another unique template for angiogenesis network formation after about 1 week. 111 Finally, a new framework for generating a neurovascular unit (NVU) (NVU consists of neurons, glial cells, blood vessels, and ECM proteins) composed of a fibrin-matrigel matrix seeded with BMECs/MSCs, which developed new blood vessels.…”
Section: Natural Biomaterials-derived Scaffoldsmentioning
confidence: 99%